STRATEGI PEMASARAN DAN PERKEMBANGAN PRODUK TABUNGAN WADI’AH DI BANK MUAMALAT KOLAKA - Safitri Febriyani; Muhammad Askari Zakariah; Suhrah Suhrah (Jurnal Ekonomi Bisnis Syariah, 2020)
The marketing strategy in selling the products used by Bank Muamalat Indonesia KCP Kolaka especially in Wadi'ah savings products is generally the same as the marketing strategy with other banks but Bank Muamalat Indonesia KCP Kolaka has its own value. The Bank has approaches to customers, whether it is a religious or emotional approach where customers see that Islamic Banks are banking financial institutions whose operations and products are developed based on the Qur'an and Hadith. What is the marketing strategy for wadi'ah savings products at Bank Muamalat Indonesia KCP Kolaka? What are the obstacles faced by Bank Muamalat Indonesia KCP Kolaka in carrying out marketing strategies? How is the development of the wadi'ah savings product at Bank Muamalat Indonesia KCP Kolaka? The aim is to find out how the marketing strategy of wadi'ah savings products at Bank Muamalat Indonesia KCP Kolaka. To find out what are the obstacles faced by Bank Muamalat Indonesia KCP Kolaka in carrying out marketing strategies. To find out how the development of wadi'ah savings products at Bank Muamalat Indonesia KCP Kolaka. Descriptive method to describe, describe, or explain the state of the object of the wadi'ah savings marketing strategy. Then the research procedures carried out included intensive observations (observations, documentation, interviews), research instruments in the form of observation sheets or notebooks, interview guidelines, documentation sheets. The data analysis techniques are in the form of data collection, data processing/data reduction using the QSPM matrix, presenting data using the QSPM method, drawing conclusions using the QSPM method. The results of the study show that in the QSPM matrix, researchers can draw the conclusion that the sequence of strategies that have the most opportunity to get customers is the pick-up strategy, personal selling, gathering, CS optimization, door to door.